DESIGN AND ANALYSIS OF BRAIN EMOTIONAL LEARNING BASED INTELLIGENT CONTROLLER (BELBIC) FOR TEMPERATURE CONTROL - Siti Rasyidah binti Syed Rabi'i, Siti Rasyidah (Universiti Teknologi Petronas, 2010)
This report presents the project undertaken to design and analyze the performance of temperature control using brain emotional learning control approach. In recent years, theory and applications of intelligent control systems have been a focus in control engineering. Among intelligent control approaches are Artificial Neural Network, Fuzzy Control and Genetic Algorithm.